The Prognosis of Axial vs. Extra-Axial Lesions on Functional Status After Traumatic Brain Injury - Quach, Nhung; Do, Jacqueline; Dirlikov, Benjamin; Ehsanian, Reza; Pasipanodya, Elizabeth C.; Ali, Arshad; Duong, Thao (Frontiers in Neurology, 2019)
Abstract Background: Head computed tomography (CT) scans are widely used in acute head injury for medical triage and surgical decisions, yet there are contradictions on the prognostic value of different head CT classifications. The intra-axial (axial) lesion versus extra-axial lesion is a well-known systemic classification but has not been applied into clinical practice since there is no evidence-based support for its prognostic value. Hypothesis: Axial injury is related to worse functional independence compared to extra-axial injury at admission to and discharge from acute rehabilitation hospitalization. Design: Observational retrospective study Settings and participants: Data from 71 participants who were enrolled at an acute rehabilitation hospital in the Northern California Traumatic Brain Injury Model System of Care (NCTBIMS) between 2005 and 2018 were included in the analysis. Main outcome measure and statistical analysis: Results of non-contrast head CT within the first 7 days after injury were analyzed to determine those with axial vs. extra-axial lesions. Functional Independence Measure (FIM) total scores were compared between the axial vs. extra-axial groups at admission and discharge using parametric and non-parametric tests. Results: There were no statistically significant group differences in FIM total scores at rehabilitation admission and discharge between the axial group and extra-axial groups. Conclusion: In this cohort of patients there was no evidence to support the hypothesis that axial injury is related to worse functional independence compared to extra-axial injury at rehabilitation admission and discharge. Utilizing MRI findings or other outcome measures, such as the 10 meter ambulation test or cognitive tests, may provide better sensitivity to potential functional differences.